Synthesis of Single Crystal LiNi0.5Mn0.3Co0.2O2 for Lithium Ion Batteries. Issue 14 (1st January 2017) - Li, Jing; Li, Hongyang; Stone, Will; Weber, Rochelle; Hy, Sunny; Dahn, J. R.
Abstract : Single crystal Li[Ni0.5 Mn0.3 Co0.2 ]O2 materials in NMC532/artificial graphite cells have excellent long term charge-discharge cycle lifetime which greatly exceeds that of conventional NMC532 materials. There are a few patents from industry regarding the synthesis of single crystal NMC. In addition, there have only been a few reports in the academic literature showing that single crystal NMC with a grain size of ∼2–5 μm having good electrochemical performance was successfully synthesized, but these workers used complex approaches. This work systematically studies the steps required to synthesize single crystal NMC materials. The key synthesis steps including the impact of the Li to transition metal ratio, sintering temperature, precursor size and sintering time are discussed. This work provides guidance for the synthesis of single crystal NMC positive electrode materials that may be suitable for lithium-ion cells with high energy density and long lifetime.